Salmonella status of eggs on the market in South-western Nigeria (2012)
The increasing prevalence of Salmonella enteritidis and the corresponding rise in human health risks necessitate the need to know the status of Salmonella in eggs sold in a major market: Bodija in Southwestern Nigeria. A total of 360 eggs were randomly bought from Bodija market. Six egg shells were pooled together to form 60 egg composites and six egg content were pooled together to form another 60 egg composites making a total of 120 egg composites. Biochemical screening, gram staining, serological identification, antimicrobial sensitivity test, coagulase, oxidase test were done in bacterial egg culture to identify Salmonella enteritidis. In all composites, 4 (3.33%) were suspected to be positive to Salmonella. Only 2 of the 4 isolates were subjected to serology and proved positive after testing with Poly “O” antiserum and Salmonella antisera “D”, so that the final proportion of egg composite sample isolated to be Salmonella was (1.66%). The strain 5v8 was very sensitive to Nitrofurantion with mean inhibition zone of (9.5mm) and totally resistant to Nalidixic acid while 3s2 was very sensitive to Nalidixic acid with mean inhibition of (12.5mm). 3s2 was resistant to Cotrimoxazole and Nitrofurantion. The two isolated strains and their replicates showed antibiotic sensitivity with a marked variation suggesting different strains of Salmonella enteritidis or genetic drift. Resistance of the two isolated strains of Salmonella enteritidis to antibiotics is of great concern to public health in treatment of infections.